2004
DOI: 10.1002/pen.20148
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the phase transition behavior of thermoplastic polyurethanes from coupled rheology/DSC measurements

Abstract: The rich behavior of thermoplastic polyurethanes (TPUs) undergoing phase transition is investigated by means of combined rheological and DSC techniques. In particular, the kinetics of micro-phase transition of a commercial TPU are followed under both isothermal conditions (crystallization from the melt), and constant temperature rate heating ramps (melting). In rheological tests, the time evolution of the storage modulus is monitored by using a strain rateϪcontrolled rheometer. The rheological results are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
3
29
1
Order By: Relevance
“…The phase transition behavior and the microstructure modification of the final solid state of the investigated thermoplastic polyurethane have been explored by measuring thermal and rheological properties during the phase transition at different annealing times and temperatures. For the sake of completeness we briefly report the main findings.…”
Section: Resultsmentioning
confidence: 99%
“…The phase transition behavior and the microstructure modification of the final solid state of the investigated thermoplastic polyurethane have been explored by measuring thermal and rheological properties during the phase transition at different annealing times and temperatures. For the sake of completeness we briefly report the main findings.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26]41 ] Most of the studies that investigate the phase transition behavior of TPUs were conducted by DSC, small angle X-ray scattering (SAXS) wide angle X-ray scattering (WAXS), infrared spectroscopy, and atomic force microcopy (AFM). [27][28][29][30][31][32][33][34] While the understanding of phase transition behaviors are important to understanding thermal postprocessing conditions, these techniques leave a gap in the relationship between exposure conditions and the physical performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal as well as flow histories can greatly affect the micro‐aggregation structure and properties of TPUs . Much effort has been spent on investigating thermal transitions and morphological changes in TPUs using different experimental techniques such as differential scanning calorimetry (DSC) , infrared spectroscopy , X‐ray scattering , and nuclear magnetic resonance spectroscopy . Some relatively recent studies have shown that rheology is also a very sensitive tool to investigate the microstructural changes taking place during the phase transition stages.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the physical and mechanical properties of TPUs depend on several factors, including the chemistry and compatibility of soft and hard segments, the ratio of soft and hard blocks, the average block lengths used and their molecular weight distribution. Thermal as well as flow histories can greatly affect the micro-aggregation structure and properties of TPUs [2][3][4][5][6]. Much effort has been spent on investigating thermal transitions and morphological changes in TPUs using different experimental techniques such as differential scanning calorimetry (DSC) [2,4,5,[7][8][9], infrared spectroscopy [2,10], X-ray scattering [7,[10][11][12][13][14], and nuclear magnetic resonance spectroscopy [2,5,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation